The Amazon in the context of school geography, a necessary discussion from student perception: The Amazon in the context of school geography, a necessary discussion from student perception - Maria da Silva , Renata (REVISTA GEONORTE, 2024)
Along the decades, the Amazon faces various forms of looting, violations and spoliation, phenomena that have intensified with the advance of capital. Through capitalist logic, it is seen only as a resource and inexhaustible source of wealth. Its particularities and sociodiversity are disregarded and, often, denied. This research is characterized as exploratory, with a qualitative-quantitative approach, the procedures used consisted of bibliographical and documentary survey and analysis and also field research. The objective of this study is to analyze how students in the 8th year of public Elementary School, located in the north of the state of Mato Grosso, perceive the Amazon in the context of School Geography. Part of the results revealed that the majority of participants identify the Amazon as a “forest”, inhabited only by “Indians and animals”, whose maintenance is very important for the production of oxygen. Regarding location, many students responded that the Amazon is in the state of Amazonas, therefore, they do not identify themselves as amazonian. The situation is worrying, as these students are unaware of the proposed theme and there is a voluntary or involuntary denial of the Amazon in their lives, a fact that can contribute to society’s neglect, disregard and lack of interest in the socio-environmental reality of the largest tropical forest in the world.